Role of feature tracking cardiac magnetic resonance imaging in early detection of cardiac dysfunction in β‐thalassemia patients recovered from COVID‐19: A cross‐sectional study - Golnaz Houshmand; Mozhgan Parsaee; Leila Najmafshar; Nadia Rajablou; Hasti T. Golroudbari; Rana Hosseini; Negar Omidi (Health Science Reports, 2024)
Abstract Background and Aims β‐Thalassemia patients may have cardiac complications due to iron overload, which puts them at higher risk of cardiac complications induced by coronavirus disease 2019 (COVID‐19) compared with the normal population. The present study aims to evaluate early cardiovascular complications following iron overload in β‐thalassemia patients who had early recovery from COVID‐19 by cardiac magnetic resonance imaging (MRI) and feature‐tracking technique. Methods Thirty‐two confirmed COVID‐19‐recovered β‐thalassemia cases were evaluated within 3 weeks to 3 months after a positive reverse‐transcriptase polymerase chain reaction COVID‐19 test. Both the heart and liver of all patients were examined using cardiac MRI. Results We analyzed 32 patients with mean age of 32.84 ± 6.45 years at baseline. Left ventricular global strain values were significantly associated with myocardial T2*. A cut‐off value of −15.08% for global longitudinal strain (GLS) with sensitivity and specificity of 90% and 61.1% (p = 0.017), 32.33% for global radial strain (GRS) with sensitivity and specificity of 80% and 94.4% (p = 0.001) and −16.21 for global circumferential strain (GCS), with sensitivity and specificity of 80% and 89.9% (p = 0.013) may indicate cardiac iron overload. Conclusion GLS, GRS, and GCS were significantly decreased in patients with myocardial T2* <20 ms (iron overload), while no significant change was observed in the right and left ventricular ejection fraction (RV‐ and LVEF). Cardiac MRI feature‐tracking may be helpful in the early detection of cardiac complications resulting from iron overload in β‐thalassemia patients who had early recovery from COVID‐19.